IMPLEMENTASI METODE PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) DENGAN MEDIA GURITA PADA PEMBELAJARAN BAHASA INDONESIA MATERI UNSUR INTRINSIK CERITA PENDEK - Aurellya Issyibilla; Maulfi Syaiful Rizal (Universitas Tribhuwana Tunggadewi, 2024)
This research aims to implement the Team Games Tournament (TGT) learning method using an octopus media on the intrinsic elements of short stories and to determine the impact of implementing this teaching method. The study employs the Team Games Tournament (TGT) method with an octopus media to examine its implementation in teaching the intrinsic elements of short stories. It adopts a qualitative approach with a descriptive method. Data collection techniques and sources include classroom observations of XI-2 at SMA Negeri 1 Kepanjen, interviews with teacher, and questionnaires distributed to students. Data analysis employs data reduction techniques, where information is summarized and essential points are identified. The findings are presented descriptively. The implementation of the teaching method with the aid of media encourages active student participation in the learning process, and students do not feel bored when reading materials or short stories presented, which also positively impacts student learning outcomes.